P09 Randomised controlled trials of community-based physical activity interventions in adults with long-term follow-up and objective physical activity measurements: a systematic review and meta-analysis. (3rd September 2019) - Wahlich, C; Chaudhry, U; Normansell, R; Cook, D; Hirani, S; Knightly, R; Harris, T
Abstract : Background: Physical inactivity is a global public health concern. Systematic review evidence indicates interventions can increase short-term physical activity (PA) levels. However, long-term health benefits require sustained increases in PA levels, and evidence from interventions with objective PA measures beyond 12-months is lacking. This review aims to: Identify and describe randomised controlled trials (RCTs) in adults with objective PA measures and long–term follow–up (beyond 12–months) Evaluate the extent to which intervention effects are sustained beyond 12–months Methods: We systematically searched seven databases using MeSH headings and keywords to identify RCTs published after 01/01/2000. We included trials reporting long-term effects (≥ 12-months) on objective PA levels with community-based participants, aged ≥18 years, with no specific medical conditions. We conducted quality assessments and meta-analyses at different follow-up points. Results: Of 17233 unique records identified, 9 studies were included in the review, 5 in the meta-analyses. Long-term follow-up ranged from 12-months to 4-years. We observed increases in PA at 12-months for steps/day (mean difference (md)=554, 95% CI=383 to 724) and weekly minutes of moderate-to-vigorous PA (MVPA) (md=34.9, 95% CI=26.9 to 42.8). This increase was sustained up to 4 years for both steps/day (md=494, 95% CI 251 to 738) and weekly minutes of MVPA (md=25.2, 95% CI=13.3 to 37.1). Conclusion: There are few PA interventions with objective follow up beyond 12-months. This review provided evidence of sustained PA intervention effects beyond 12-months and up to 4-years for both steps/day and MVPA.